A structural equation model of the halal certification and its business performance impact on food companies - Salindal, Normia Akmad; Ahmad, Mohd Ismail Sayyed; Abdullah, Kalthom; Ahmad, Badruddin Paguimanan (IIUM Press, International Islamic University Malaysia, 2018)
Despite the overwhelming popularity of halal certification, there is considerable confusion surrounding its role and business value as well as its relation to business performance. Thus, the aim of this study is to gain better understanding of the relationship between halal certification and the business performance of halal certified food companies in the Philippines. The study was based on a survey and the time horizon was cross-sectional. The survey was carried out using stratified sampling on halal certified food companies operating in the Philippines. Through a self-administered questionnaire, 141 usable responses were acquired from the responding companies. The theorized relationship of halal certification and business performance was tested using confirmatory factor analysis and structural equation modeling (SEM). The findings of this study revealed that halal certification significantly affect business performance of halal certified food companies in terms of innovative and financial performance. It was also revealed that innovative performance fully mediates the relationship between halal certification and financial performance.